Phase II randomized trial of capecitabine with bevacizumab and external beam radiation therapy as preoperative treatment for patients with resectable locally advanced rectal adenocarcinoma: long term results - Ramón Salazar; Jaume Capdevila; Jose Luis Manzano; Carles Pericay; Mercedes Martínez-Villacampa; Carlos López; Ferrán Losa; María José Safont; Auxiliadora Gómez-España; Vicente Alonso-Orduña; Pilar Escudero; Javier Gallego; et al. (BMC Cancer, 2020)
Abstract Background Preoperative chemoradiotherapy with capecitabine is considered as a standard of care for locally advanced rectal cancer. The “Tratamiento de Tumores Digestivos” group (TTD) previously reported in a randomized Ph II study that the addition of Bevacizumab to capecitabine-RT conferred no differences in the pre-defined efficacy endpoint (pathological complete response). We present the follow-up results of progression-free survival, distant relapse-free survival, and overall survival data at 3 and 5 years. Methods Patients (pts) were randomized to receive 5 weeks of radiotherapy (45 Gy/25 fractions) with concurrent Capecitabine 825 mg/m2 twice daily, 5 days per week with (arm A) or without (arm b) bevacizumab (5 mg/kg once every 2 weeks). Results In our study, the addition of bevacizumab to capecitabine and radiotherapy in the neoadjuvant setting shows no differences in pathological complete response (15.9% vs 10.9%), distant relapse-free survival (81.0 vs 80.4 and 76.2% vs 78.2% at 3 and 5 years respectively), disease-free survival (75% vs 71.7 and 68.1% vs 69.57% at 3 and 5 years respectively) nor overall survival at 5-years of follow-up (81.8% vs 86.9%). Conclusions the addition of bevacizumab to capecitabine plus radiotherapy does not confer statistically significant advantages neither in distant relapse-free survival nor in disease-free survival nor in Overall Survival in the short or long term. Trial registration EudraCT number: 2009–010192-24 . Clinicaltrials.gov number: NCT01043484 .